The Influence of Content Marketing Quality on Consumer Loyalty Toward the Fashion Brand Zaafer - Yusuf Al Qardhawi; Erlita Ridanasti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of content marketing quality on consumer brand loyalty toward the fashion brand Zaafer by examining informative value, entertainment value, and social value as independent variables, with experiential evaluation as a mediating variable. A quantitative approach was employed through an online survey distributed to 211 respondents who are active TikTok users and have purchased Zaafer products. Data analysis was conducted using Partial Least Square Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings reveal that informative value, entertainment value, and social value significantly influence experiential evaluation. Furthermore, experiential evaluation significantly impacts brand loyalty. These results suggest that high-quality content marketing on social media platforms, particularly TikTok, plays a crucial role in strengthening consumer loyalty to the Zaafer brand. This study contributes to the development of digital marketing strategies by emphasizing the imporance of delivering content that is relevant, entertaining, and socially engaging.